Pengoptimalan Potensi UMKM Pasca Covid 19 di Wilayah Kelurahan Kauman Kecamatan Prajurit Kulon Kota Mojokerto - Hariani, Mila; Irfan, Mochamad; Al Hakim, Yusuf Rachman; Sagita, Dwi Simbe; Kurnianingtyas, Wulan (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Community service activities during the post-Covid 19 pandemic focused on MSMEs in the Kauman Village area, Warrior Kulon District, Mojokerto City who were affected by the Covid 19 event. Community service activities were carried out as a form of concern for MSMEs who lost income due to the Covid 19 pandemic. Community service activities were carried out as a forum to provide assistance in the form of knowledge to the community, especially MSMEs. This community outreach activity was carried out by several lecturers and students at the University of Mayjen Sungkono Mojokerto. This training was attended by 15 MSMEs in the Kauman sub-district, Soldier Kulon sub-district, Mojokerto City. The implementation of community service activities is carried out for approximately 8 hours. MSMEs can optimize sales and get additional income for post-covid 19 financial income, by providing training starting from the start of production, packaging, taking product photos and digital marketing by using and following current technological developments such as websites. In addition, this activity was also carried out to build good relations between the surrounding community and the University of Mayjen Sungkono Mojokerto.